Oral Anticoagulants After Ischemic Stroke in Older Adults with Atrial Fibrillation (Ictus, 2022)
Letter to the editor about Oral Anticoagulants After Ischemic Stroke in Older Adults with Atrial Fibrillation, published in Ictus volume 3 issue 2.
Keywords: anticoagulation; ischemic stroke; direct anticoagulants